Potentially Toxic Trace Elements in the Urban Soils of Santiago de Compostela (Northwestern Spain) - Herbón, Cecilia; Barral, María Teresa; Paradelo, Remigio (Applied sciences, 2021)
With the objective of increasing information inorganic pollutants in urban soils in Spain, we studied the presence of Cu, Pb, Zn, Ni, Cr, and As in 55 soils in the city of Santiago de Compostela (northwestern Spain). The soils were developed over diverse parent materials (granites, gneiss, schists, and amphibolites) and present different land uses, urban grasslands, urban forests, urban allotment gardens, and peri-urban agricultural soils. Total trace element concentrations, analyzed by XRF of ground samples, were correlated to physicochemical properties of the soils, and the influence of land use, lithology, and location on the degree of pollution was explored. In most soils, trace element concentrations followed the sequence Zn (55–484 mg kg−1) > Pb (20–566 mg kg−1) > Cr (17–277 mg kg−1) > Cu (17–188 mg kg−1) > As (13–205 mg kg−1) > Ni (11–91 mg kg−1). The concentrations were overall higher than regional backgrounds, but not high enough to class the soils as contaminated according to the Spanish regulation. Accordingly, the geoaccumulation index values indicate that most soils present low to moderate pollution levels. Among the elements studied, Cu, Pb, and Zn were correlated between them, with their highest concentrations happening in soils of the green areas in the city center; Cr and Ni concentrations were related to lithology of the parent material, with the highest concentrations in soils developed over amphibolite; finally, As concentrations are higher in two precise points without a clear connection to a known source of pollution.